Induction of ROS and DNA damage-dependent senescence by icaritin contributes to its antitumor activity in hepatocellular carcinoma cells. (1st January 2019) - Wang, Shikang; Wang, Qian; Wang, Huijun; Qin, Chengkun; Cui, Xianping; Li, Lei; Liu, Yongqing; Chang, Hong
Abstract: Context: Icaritin (ICT), a prenylflavonoid derivative extracted from the Epimedium (Berberidaceae) genus, has been identified to exhibit antitumor effect in hepatocellular carcinoma (HCC) cells by inducing apoptosis. However, its effect on cellular senescence has not been elucidated. Objective: To investigate the mechanism for low concentrations of ICT exerting antitumor activity through induction of cellular senescence. Materials and methods: Human HepG2 and Huh7 cells were treated with low concentrations of ICT (1 and 2 μM) once per day for a week. Cellular senescence was evaluated through cell viability and senescence-associated-β-galactosidase activity. Cell cycle distribution and ROS levels were measured with flow cytometry. Gene expression was detected using qRT-PCR and western blotting. Fluorescent punctuates formation of γH2AX was analyzed by immunofluorescence. Results: ICT (1 and 2 μM) promoted cellular senescence in HepG2 and Huh7 cells, as observed by enlarged and flattened morphology and increased senescence-associated-β-galactosidase activity (∼7-8-fold and ∼11-12-fold of vehicle controls, respectively), accompanied by significant cell cycle arrest and decrease in DNA synthesis. Mechanistically, ICT-induced senescence occurred through accumulation of ROS (∼1.3-fold and ∼1.8-fold of vehicle controls in response to 1 and 2 μM ICT, respectively), which further resulted in DNA damage response, as evidenced by strong induction of γH2AX through immunofluorescence and western blotting assays. Pharmacological inhibition of ROS production with N -acetylcysteine attenuated ICT-induced γH2AX and senescence-associated-β-galactosidase activity (∼0.28-0.30-fold decrease, p < 0.05). Discussion and conclusions: Induction of cellular senescence by ICT defines a novel anticancer mechanism of ICT and provides a rationale for generalizing the study design to a broader study population to further developing ICT as a novel therapeutic agent for treatment of HCC.